A new surgical technique to treat corneal perforations using amniotic membrane and surgical adhesive - Pontes, K. C. S.; Borges, A. P. B.; Eleotério, R. B.; Frazão, A. C. N.; Machado, D. P. D.; Reis, E. C. C.; Sepúlveda, R. V.; Duarte, T. S.; Laus, J. L. (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2014)
The objectives of this study were to compare surgical techniques and the effects of using n-butyl 2-cyanoacrylate and bovine amniotic membrane to repair perforated lesions in corneas. Penetrating keratoplasty was performed in sixty New Zealand White rabbits under general anesthesia. Group 1 (G1) was treated with n-butyl 2-cyanoacrylate, group 2 (G2) received a fragment of amniotic membrane through the anterior chamber and application of n-butyl 2-cyanoacrylate over the lesion, group 3 (G3) was treated with the same technique as G2 with the addition of an amniotic membrane bandage covering the cornea and sutured in the limbus region, and group 4 (G4) was treated with an amniotic membrane sutured to the lesion and an amniotic membrane bandage sutured in the limbus region. Clinical, histological and histomorphometric examinations of the corneas were performed. The membrane acted as a barrier for aqueous humor in G2 and G3, thereby keeping the surface dry for adhesive application; it also prevented the adhesive from contacting intraocular structures. The groups treated with amniotic membrane and surgical adhesive showed better results than the groups treated with either material alone. Thus, the combination of the membrane with the adhesive is recommended for this type of lesion.

Os objetivos deste estudo foram comparar técnicas cirúrgicas e efeitos do n-butil 2-cianoacrilato e da membrana amniótica bovina na reparação de lesões perfuradas em córneas. Sessenta coelhos da raça Nova Zelândia Branca foram submetidos à ceratoplastia penetrante sob anestesia geral. O grupo 1 (G1) foi tratado com n-butil 2-cianoacrilato; o grupo 2 (G2) recebeu um fragmento de membrana amniótica pela câmara anterior e aplicação de n-butil 2-cianoacrilato sobre a lesão; o grupo 3 (G3) foi tratado com a mesma técnica aplicada ao G2, adicionando-se uma bandagem de membrana amniótica cobrindo a córnea e suturada à região do limbo; e o grupo 4 (G4) foi tratado com membrana amniótica suturada nas bordas da lesão e bandagem de membrana amniótica suturada na região do limbo. Foram realizados exames clínico, histológico e histomorfométrico. A membrana atuou como barreira contra o extravasamento do humor aquoso nos grupos 2 e 3, manteve a superfície seca para posterior aplicação do adesivo e impediu o contato do adesivo com as estruturas intraoculares. Os grupos tratados com o adesivo associado à membrana amniótica demonstraram melhores resultados do que aqueles tratados com cada material isoladamente. Assim, a combinação da membrana com o adesivo é indicada neste tipo de lesão.
Keywords: Rabbits; Cornea; Cyanoacrylate; Glycerin; Ophthalmic surgery; Coelhos; Córnea; Cianoacrilato; Glicerina; Cirurgia oftálmica